Diabetes mellitus-driven pulmonary injury: multidimensional mechanisms linking metabolic dysregulation to gut-lung axis and promising therapies - Sun, Jiacheng; Chen, Junyang; Shen, Yuntian; Yao, Xinlei; Sun, Hualin; Chen, Bingqian; Feng, Jian (Frontiers in Pharmacology, 2025)
Diabetes mellitus (DM), a globally prevalent metabolic disorder, poses a significant public health threat due to its systemic complications. Recent studies have increasingly recognized the lung as a target organ in diabetic pathology. However, owing to the respiratory system’s complex physiology, the mechanisms underlying DM-associated lung injury remain poorly understood and require further investigation. This review systematically elucidates the multifaceted effects of DM-induced metabolic disturbances on the lung, with a focus on four key pathophysiological axes triggered by hyperglycemic homeostasis, including chronic inflammation, oxidative stress imbalance, endocrine network disruption, and intestinal dysbiosis. Building upon the “metabolism-microbiota-immune” axis framework, this study demonstrates that: persistent hyperglycemia induces pulmonary tissue damage and immune microenvironment disruption through metabolite accumulation and mitochondrial dysfunction; DM-associated intestinal dysbiosis amplifies pulmonary inflammation via the gut-lung axis, mediated by metabolic reprogramming and immune cell trafficking; and metabolic aberration-driven dysregulation of innate/adaptive immunity serves as the pivotal mediator for progressive lung injury. Building on this mechanistic framework, we discuss emerging therapeutic avenues that target metabolic reprogramming, modulation of the gut microbiota, and restoration of immune homeostasis. Promising strategies include repurposed antidiabetic drugs (e.g., SGLT-2 inhibitors, GLP-1 receptor agonists), microbiome-targeted therapies (e.g., fecal microbiota transplantation), and novel immunomodulatory agents. These therapies are offering a new shift towards multi-target treatments for diabetic pulmonary complications.